PENGGUNAAN MODEL LEARNING CYCLE 7E BERBANTUAN CONCEPTUAL CHANGE TEXT UNTUK MEREMEDIASI MISKONSEPSI PADA MATERI CAHAYA - Febriana Nyuragi; Tomo Djudin; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to calculate the effectiveness of remediation using the learning cycle 7E model assisted by conceptual change text on light material at SMP Negeri 2 Ledo. The form of research used is one group pretest posttest design. The data collection technique used is by collecting data from the test results given before and after remediation. The sample in this study amounted to 23 students. The data collection tool is in the form of multiple choice with open reason totaling 9 questions. Based on the data analysis, the average percentage reduction in misconceptions after remediation was 28,98%. Based on the calculation of the Mc. Nemar test (???????????????????????????????????????????????? 2 = 6,705 > ???????????????????????? 2 = 3,84) dan Binomial test (???? = 0,0086 < ???? = 0,05) it can be said that there was a significant conceptual change. Based on the calculation of effectiveness using the price of the proportion of decreasing the number of misconception, the result obtained f=0,49 in the medium category. Overall, researcher can draw the conclusion that the use of the learning cycle 7E model assisted by conceptual change text is effective in remediating student misconceptions on the light material.Keywords: Learning Cycle 7E, Conceptual Change Text, Remediation